Systems biology approaches investigating mitochondrial dysfunction in cyanotic heart disease: a systematic reviewResearch in context - Malak Elbatarny; Yu Tong Lu; Mostin Hu; John Coles; Seema Mital; Amanda Ross-White; Osami Honjo; David J. Barron; Anthony O. Gramolini (EBioMedicine)
Summary: Background: Cyanotic congenital heart disease (CCHD) affects over 3 million individuals globally and can progress to heart failure. Mitochondrial dysfunction is well established in adult heart failure and is also a central feature of CCHD. CCHD cyanosis itself contributes to further mitochondrial dysfunction. Systems biology methods detail the epigenomic, transcriptomic, and metabolomic profile of biological samples. This systematic review highlights CCHD systems biology literature related to mitochondrial dysfunction. Methods: OVID/Medline was searched between January 2010 and June 2025. Studies implementing untargeted systems biology methods in CCHD tissue or plasma were included. Genes with differential expression between CCHD and unaffected controls were pooled and analysed using GO term functional enrichment for pathway analysis, transcription factor and kinase enrichment, and metabolic pathways. Findings: From 31 included studies (genomic: n = 5, epigenomic: n = 3, transcriptomic: n = 23, proteomic: n = 2, metabolomic: n = 3, lipidomic: n = 1), we identified 8 pathogenic/likely pathogenic single nucleotide polymorphisms, 73 differentially methylated genes, 4170 differentially expressed genes, 173 differentially expressed proteins between CCHD versus unaffected controls. Several genes involved in mitochondrial respiratory chain (NDUFV1, NDUFV2, NDUFA5, NDUFS3, COX5A, COQ7) were identified. Interpretation: CCHD pathogenesis and progression are associated with mitochondrial dysfunction through changes in metabolism, fission, and fusion. Funding: Vanier CIHR Scholarship, UHN Research Studentship, and Ontario Graduate Scholarship. Translational Biology and Engineering Program seed operating funds and research funding from the Heart and Stroke Foundation of Canada.